Molecular fingerprinting of the myxozoan community in common carp suffering Swim Bladder Inflammation (SBI) identifies multiple etiological agents - Holzer, Astrid S (BioMed Central, 2014)
BACKGROUND: Swim bladder inflammation (SBI) is an important disease of common carp fingerlings in Central Europe. In the 1980s, its etiology was ascribed to multicellular proliferative stages of the myxozoan parasite Sphaerospora dykovae (formerly S. renicola). S. dykovae was reported to proliferate in the blood and in the swim bladder prior to the invasion of the kidney, where sporogony takes place. Due to the presence of emerging numbers of proliferative myxozoan blood stages at different carp culture sites in recent years we analysed cases of SBI, for the first time, using molecular diagnostics, to identify the myxozoan parasites present in diseased swim bladders. METHODS: We amplified myxozoan SSU rDNA in a non-specific approach and compared the species composition in swim bladders at culture sites where carp demonstrated 1. No signs of SBI, 2. Minor pathological changes, and 3. Heavy SBI. Based on DNA sequences, we determined the localisation and distribution of the most frequent species by in situ hybridisation, thereby determining which myxozoans are involved in SBI. RESULTS: Large multicellular myxozoan swim bladder stages characterised heavy SBI cases and were identified as S. dykovae, however, blood stages were predominantly represented by Sphaerospora molnari, whose numbers were greatly increased in carp with mild and heavy SBI, compared with SBI-free fish. S. molnari was found to invade different organs and cause inflammatory changes also in the absence of S. dykovae. One site with mild SBI cases was characterised by Buddenbrockia sp. infection in different organs and a general granulomatous response. CONCLUSIONS: We provide evidence that the etiology of SBI can vary in relation to culture site and disease severity and that emerging numbers of S. molnari in the blood represent an important co-factor or precondition for SBI.